THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND FINANCIAL SELF-EFFICACY ON STUDENTS FINANCIAL MANAGEMENT - Nurjaman, M Jujun; Hafni, Diska Arliena (Universitas Bunda Mulia, 2025)
Background: Financial management is a crucial aspect, especially for students. Accounting students as someone who has a basic understanding of finance, are expected to be able to manage their finances well. However, the level of financial literacy among students is still quite low. Therefore, this study aims to complement the existing literature, by finding out how Financial Knowledge, Financial Attitude, and Financial Self-Efficacy affect the Financial Management of accounting students in Yogyakarta.Objective: This study aims to determine the effect of Financial Knowledge, Financial Attitude, and Financial Self-Efficacy on Financial Management in accounting students in Yogyakarta.Research Methods: This study uses a quantitative method, with a questionnaire as a data collection technique. Data analysis is using multiple linear regression with SPSS V.21 Software.Research Results: The results of the study indicate that Financial Knowledge, Financial Attitude, and Financial Self-Efficacy have a positive effect on Financial Management.Originality/Novelty of Research: This study uses two theories, namely the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT) to understand how students' financial management behavior. All previous studies that are references only use one theory in explaining financial management behavior. In addition, this study also focuses on accounting students in Yogyakarta.